Innovation in Technology in HRM - Mat Rashid, Kartini (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2022)
In today's COVID-19-affected situation, there are many changes that occur in the workplace. At the same time, many innovations are created to improve system performance and management in organisations. Innovation has to do with restructuring plans or methods in management to achieve organisational goals. It also includes modifying current ideas and ways of handling management. For example, management leaders introduce new systems for recording data to improve efficiency. Furthermore, system improvements can help organisations to achieve competitive advantages and make companies' reputations higher than other companies. Innovation can be defined as developing new strategies to further longterm goals within the organisations.